Calculations of the Strains and Thicknesses of Pipe Elbows on the Basis of Expressions Resulting from the EU Directive for the Case of Large Strains - ŚLODERBACH, Zdzisław (Engineering Transactions, 2015)
The relations to calculate the maximum value of relative strains, which occur in a process of bending of tubes on benders, in stretched layers of tubes, are presented in this work on the basis of the EU Directive concerning production of pressure equipment. It has been shown that for large deformations that occur during bending of the pipes on knees, logarithmic strain measures (real) and relative strain measures give different values of strain and equal wall thicknesses in the bending zone. Reverse expressions were also derived to calculate the required initial wall thickness of the tube to be bent, in order to obtain the desired wall thickness of a knee after bending.